High-resolution biostratigraphic zonation across the Cretaceous/Paleogene (K/Pg) boundary from the Sulaymaniyah area, Kurdistan Region, Northeastern Iraq - Ghafor, Imad M.; Mustafa, Asaad I.; Mohialdeen, Ibrahim M.; Mansurbeg, Howri (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
The present study interprets the high resolution of the biostratigraphy across the Cretaceous/Paleogene (K/Pg) boundary from Sulaymaniyah, Kurdistan Region, and north-east Iraq, based on planktic foraminifera. The Dartw section was selected for this study, within the High Folded Zone. The biozone contact consists of lithostratigraphic resemblance and is represented by the upper part of the Tanjero Formation (late Maastrichtian) with the overlying Kolosh Formation (Danian). Four late Maastrichtian planktic foraminiferal biozones have been recorded from the Tanjero Formation: Racemiguembelina fructicosa Interval Zone (CF4), Pseudoguembelina hariaensis Concurrent Range Zone (CF3),Pseudoguembelina palpebra Partial Range Zone (CF2), and Plummerita hantkeninoides Total Range Zone (CF1), while three Danian planktic foraminiferal biozones and two subzones have been recorded from the Kolosh Formation: (Guembelitria cretacea (P0) Interval Zone, Parvularugoglobigerina eugubina (Pα) Total Range Zone, and Parasubbotina pseudobulloides (P1) Partial-Range Zone (Globoanomalina archaeocompressa (P1a) Partial Range Subzone, and Subbotina triloculinoides (P1b) Interval Subzone). High biostratigraphic resolution indicates a complete K/Pg transition with no hiatus at the studied section in the Sulaymaniyah area. The ranges of the species recognized in this study are given. Correlations with other sections in Iraq and other parts of the world, including the typeMaastrichtian and Danian areas, are discussed and represented in correlation charts, together with the ranges of the important Upper Maastrichtian and Paleocene species.